Newborn hearing screening programme based on an integrated hospital and community care system. Results of the first 4 years of activity. (February 2021) - Palma, Silvia; Roversi, Maria Federica; Alberici, Maria Paola; Negri, Maurizio; Chiossi, Claudio; Berardi, Alberto; Genovese, Elisabetta
Abstract: Since January 2012, babies born in the province of Modena, Italy, have routinely undergone hearing testing as part of a two-stage screening programme. Newborn hearing screening (NHS) has been based on an integrated hospital and community care system and this study aims to assess screening coverage, referral rates, the prevalence, type and extent of hearing loss several years into the programme. Data were collected from January 1, 2012 to December 31, 2015. Coverage was over 99% in all five facilities of the province. The ratio of "fails of the screening" to the total number of infants tested varied over the period from 1.2% to 0.9% in the third level facility, and from 0.8% to 0.4% in the other four. Although hearing loss was mainly associated with dysmorphic\syndromic diseases or a family history of hearing loss, some 23% of cases were identified with no known risk factors. We highlight the importance of the NHSP and the need for strong support from healthcare administrators to ensure high coverage. This is especially true since although the prevalence of hearing loss was higher among infants with audiological risk factors, several cases of hearing loss were found in newborns with no known risk factors.